(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The article consider the ideological and symbolic features of the teachings of new Christian movements. The emergence of new Christian movements is associated with the incompatibility of traditional Christianity, its religious rites and rituals with the requirements of the time or in general with the crisis of Christian culture. In this regard, the study analyzes the ideological and symbolic features of the new Christian cults, their relationship to the main Christian canons, as well as changes in religious rituals and rites. As a result of studying the ideological and symbolic features of the new Christian currents, the authors come to the following conclusions. Firstly, the main features of the new religious movements are in relation to the creeds of traditional Christianity, to the Holy Trinity, and to the performance of the seven sacraments.Secondly, new religious movements are distinguished by their simplicity of religious sermons, vivid performance of religious rites and rituals. Thirdly, new religious trends attach great importance to visual elements. Their logos, flags, emblems and other religious symbolic attributes are closely related to the history of their development. They are based on the ideology of Protestantism and Freemasonry.To sum up, the ideological and symbolic content of new religious movements is transformed in accordance with the requirements of society and time. Key words: Christianity, new religious movements (NRM), symbols of faith, eschatology, worship, religious emblems and logos.